Ribonuclease RNase Z is an evolutionarily conserved deAMPylase - Meghomukta Mukherjee; Alex Pon; Timea Goldberg; Krzysztof Pawłowski; Anju Sreelatha (Proceedings of the National Academy of Sciences, 2025)
Protein AMPylation is a highly conserved posttranslational modification in which adenosine monophosphate (AMP) is covalently attached to protein substrates. Our studies revealed that the mitochondrial AMPylase, Selenoprotein O (SelO), regulates cellular metabolism and oxidative stress response through AMPylation of key metabolic enzymes. Remarkably, SelO-mediated AMPylation is conserved in bacteria and humans, yet the enzyme that removes the AMP from modified proteins remains unknown. We show that the ribonuclease, RNase Z, is both necessary and sufficient to catalyze deAMPylation of AMPylated substrates. These results establish RNase Z as a moonlighting enzyme with previously unrecognized functional roles beyond tRNA processing, expanding our understanding of its biological significance. Furthermore, identification of an evolutionarily conserved deAMPylase highlights the importance of reversible AMPylation as a biological regulatory mechanism, akin to well-studied post translational modifications such as protein phosphorylation.